(untitled) (International Journal of Ayurveda and Pharma Research, 2023)
Millets are a group of small seeded ancient crops packed with various nutrients, providing health benefits. It is classified under Kshudra dhanya in Ayurveda. Food and Agriculture organization and United Nations has announced 2023 as International year of millets and Government of Indian also proposed to celebrate 2023 as International year of millets. Aim: To study and analyze the various types of millets and their health benefits, described in various ancient Samhita. Objective: To study the properties, carbohydrate value and other nutritional value of the various millets. Material and Methods: The Bruhattrayi & Laghuttrayi, modern medical textbooks, journals and online database was reviewed for this purpose. Results & Conclusion: Millets are good source of protein, fiber, key vitamins & minerals. They are helpful in weight management, preventing various diseases such as obesity, diabetes, cardiovascular disease and inflammation of gut etc.